THE ANALYSIS OF FACTORS ON STUDENTS’ SATISFACTION: THE CASE OF MONGOLIA - Tsogtsuren, Bayasgalan (Applied Studies in Agribusiness and Commerce, 2025)
Our study aims to examine the correlation between professors’ communication, professors’ knowledge, professors’ skills, teaching method and campus environment and how students’ issues are assessed with their satisfaction. We attempt to evaluate the students’ satisfaction of the  Mongolian State University of Educational and Royal International University, Mongolia.  Our study was conducted via online channel from 326 respondents, who study at university bachelor degree in Mongolian public and private university.  We used SMART PLS-3.0 and SPSS-25.0 software as a qualitative research program, Cronbach's alpha (α coefficient), (T statistic) and (P values) were used to measure the data in our study. There were two hypotheses are supported and three hypotheses are no supported in our study. In conclusion, RQ 1 and RQ 4 are strongly supported by the path analysis results, while RQ 2, RQ 3, and RQ 5 do not find sufficient evidence to assert their influence on student satisfaction based on the analyzed data.